Effect of Microstructure Control of Thin Film Yttria Stabilized Zirconia Electrolyte for Solid Oxide Fuel Cells by Adjusting Oblique Angle and Target Substrate Distance of Sputtering Process. (10th July 2019) - Lee, Sanghoon; Yu, Wonjong; Cho, Gu Young; Cha, Suk Won
Abstract : In the present study, thin film yttria stabilized zirconia (YSZ) electrolyte was fabricated for solid oxide fuel cells via radio frequency (RF) magnetron sputtering with variation in oblique angle and target substrate distance (TSD). Growth tendencies were differentiated through adjusted oblique angle and TSD during sputtering, thereby microstructure of YSZ was changed. Electrochemical behavior of microstructure-controlled thin film YSZ was investigated by means of applying YSZ to anodic alumina oxide (AAO) based solid oxide fuel cells (SOFC). On nanoporous AAO substrates, Pt anode, YSZ electrolyte, and Pt cathode were deposited serially all through sputtering. For depositing thin film YSZ electrolyte, oblique angle and TSD were differentiated into four cases each, while thickness was set to be equal. YSZ thin films were evaluated using FESEM, AFM, FIB-SEM, XRD, and XPS. Electrochemical performance was investigated through i-V plot and EIS.